Application of Fuzzy-Sets Integral in Expert Systems - Dervinienė, A.; Bagdonas, V.; Daunoras, J. (Elektronika ir Elektrotechnika, 2007)
In more situations for decision-making the methods based on expert estimations are used, that is, human intellect is being used as a measuring instrument. The decision risk level dependent on expert’s facilities (defined with the consistency and competence criterions) must be known in the decision-making process. The methodology of experts decisions risk level estimation’s is discussed. The methodology is based on search and use of experts’ consistency and competence rates, what can be get applying excess of the experts offered information. The application of Sugeno and Choquet fuzzy integrals for processing group expert estimations are offered. Ill. 1, bibl. 4 (in English; summaries in English, Russian and Lithuanian).